1978
DOI: 10.1073/pnas.75.9.4078
|View full text |Cite
|
Sign up to set email alerts
|

Coordination environment and fluoride binding of type 2 copper in the blue copper oxidase ceruloplasmin.

Abstract: The electron paramagnetic resonance (EPR) spectra of the blue copper oxidase ceruloplasmin ferroxidase, iron(II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The T2 copper exhibits EPR parameters typical for normal copper ( A ∥ = 158−201 × 10 -4 cm -1 ) and no intense features in the visible absorption spectrum. An archetypal feature of the T2 site in the multicopper oxidases is its ability to bind F - with an unusually high affinity, a feature which can easily be identified by the 50 × 10 -4 cm -1 superhyperfine splitting observed in the EPR spectrum ( vide infra ). The potential of the T2 site has been reported only for R. vernicifera Lc, wherein it is 365 mV . The T3 copper pair has an absorption band at around 330 nm (ε ≈ 5000 M -1 cm -1 ) and is EPR-silent, indicative of a strongly antiferromagnetically coupled Cu(II) pair bridged by a hydroxide.…”
Section: Multicopper Oxidasesmentioning
confidence: 99%
“…The T2 copper exhibits EPR parameters typical for normal copper ( A ∥ = 158−201 × 10 -4 cm -1 ) and no intense features in the visible absorption spectrum. An archetypal feature of the T2 site in the multicopper oxidases is its ability to bind F - with an unusually high affinity, a feature which can easily be identified by the 50 × 10 -4 cm -1 superhyperfine splitting observed in the EPR spectrum ( vide infra ). The potential of the T2 site has been reported only for R. vernicifera Lc, wherein it is 365 mV . The T3 copper pair has an absorption band at around 330 nm (ε ≈ 5000 M -1 cm -1 ) and is EPR-silent, indicative of a strongly antiferromagnetically coupled Cu(II) pair bridged by a hydroxide.…”
Section: Multicopper Oxidasesmentioning
confidence: 99%
“…Alternatively, F Ϫ -bound forms of different MCOs exhibit very similar spectral features, where F Ϫ binds strongly (K b Ϸ 10 5 M Ϫ1 ) at the 3 -position of the trinuclear site (13,20,28,30). With its small size and high affinity, F Ϫ would bind to the trinuclear site unobstructed by the protein environment (N 3 Ϫ has an Ϸ200-fold lower K b ).…”
mentioning
confidence: 99%
“…In fungal laccase, plant laccase, ascorbate oxidase, and human Cp it was previously found that two fluoride ions bind selectively to the T2 copper site, one with high affinity and one with low affinity ( ). This is seen by EPR, in which fluoride-binding induces a superhyperfine splitting of about 50 × 10 -4 cm -1 in the low-field hyperfine line of the T2 copper.…”
Section: Resultsmentioning
confidence: 99%